1990
DOI: 10.1111/j.1600-0447.1990.tb06465.x
|View full text |Cite
|
Sign up to set email alerts
|

Slower theta activity over the midfrontal cortex in schizophrenic patients

Abstract: Disturbances of the topographical distribution of theta activity in the EEG spectra before and during voluntary movements were investigated in 31 neuroleptic-treated and in 13 untreated schizophrenics and matched controls as well as in 15 normals medicated with haloperidol. All 4 groups demonstrated similar topographical distribution of theta mean power density, with highest values over the midfrontal region. In the center frequency of the theta band, however, treated and untreated schizophrenics had lower val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 25 publications
1
12
0
3
Order By: Relevance
“…However, an EEG study by Small et al (1987) in treatment resistant schizophrenic patients revealed no EEG differences between chronic drug-free schizophrenic patients and healthy volunteers, but a significant difference in terms of increased amplitudes in the delta and theta frequency bands between placebo and three antipsychotics. These findings support the impact of our data as well as other studies investigating the influence of antipsychotics treatment on EEG patterns (Westphal et al, 1990;Matsuura et al, 1994;Centorrino et al, 2002).…”
Section: Discussionsupporting
confidence: 94%
“…However, an EEG study by Small et al (1987) in treatment resistant schizophrenic patients revealed no EEG differences between chronic drug-free schizophrenic patients and healthy volunteers, but a significant difference in terms of increased amplitudes in the delta and theta frequency bands between placebo and three antipsychotics. These findings support the impact of our data as well as other studies investigating the influence of antipsychotics treatment on EEG patterns (Westphal et al, 1990;Matsuura et al, 1994;Centorrino et al, 2002).…”
Section: Discussionsupporting
confidence: 94%
“…Changes in brain rhythms have been associated with various disorders (Westphal et al, 1990;Helkala et al, 1991;Mizuki et al, 1992;Suetsugi et al, 2000;Grunwald et al, 2001;Koenig et al, 2001) but, until very recently, ''despite extensive work on the behavioral and physiological correlates of brain rhythms, it is still unresolved whether they have any important function in the mammalian cerebral cortex'' (Sejnowski and Paulsen, 2006). Further, rhythmicity need not have a function since synchronous oscillation may be ''a continuum property of large fields of interconnected cells'' (Robinson et al, 1998).…”
Section: Introductionmentioning
confidence: 97%
“…A predominance of delta and theta activity has been reported over posterior scalp sites (e.g., Harris et al 1997;Ulrich and Otto 1984;Westphal et al 1990), but also at central (Karson et al 1987(Karson et al , 1988, left lateral (Schellenberg et al 1989), frontal (Gattaz et al 1992), or frontotemporal (Serafetinides 1984) electrodes. Some studies emphasize that the distribution of slow wave activity is generally diffuse or variable (Elbert et al 1992;Fenton et al 1980;Galderisi et al 1991;Macmahon and Walter 1938).…”
Section: Introductionmentioning
confidence: 97%